Concept of International Legal Policy in Foreign Comparative Legal Studies - O. S. Magomedova (Московский журнал международного права, 2020)
INTRODUCTION. International legal policy is a new object in international legal studies, although this phenomenon exists as long as the external relations of States. International legal policy is a rare case of research subject, which remains unexplored. International legal policy as a Concept of State's policy towards legal aspects of international relations was formed in the 80-s of last century. Earlier the questions and their particular aspects now embraced by international legal policy were divided between international lawyers and international relations researchers. However international legal policy is an integral system of State's approaches to international legal matters, therefore its punctual research is relevant only from comparative point of view. It would be interesting to compare States' positions on concrete issues or States' tactics at different stages of realization of international legal norms. This article concerns the question whether comparative studies of international legal policy can be integrated into existing fields of comparative foreign relations law or of comparative research of international law.MATERIALS AND METHODS. The article surveys theoretic questions primarily on the base of doctrinal sources. The retrospective analysis of the comparative method in international law is based on works published by Russian and foreign experts during the XX century. Particular attention is drawn upon works of founders of comparative research in international legal studies. The concept of foreign relations law in the scholarship and practice of the U.S. is researched on the base of national case law, which formulated the principle of executive exceptionalism in State foreign policy. Research work is realized with the use of analysis, synthesis, systematisation, as well as methods of historical and comparative method.RESEARCH RESULTS. The Article consistently reveals meaning and the content of international legal policy as one of the authors of the concept, French lawyer and diplomat G. de Lacharriere, presented it. The Article examines the history of foreign relations law in the U.S. and presents its doctrinal estimations from viewpoint of American constitutional law. The research work specifies different points of view on content of foreign relations law and approaches to its justification. Indeed international legal policy and foreign relations law can be compared as two types of State’s approach to its legal position on the international scene. There are six parameters for comparison: sources, functions, subjects of both concepts, questions on allocation of foreign powers in the State, on relationship between international and national law, on the role of national courts in interpretation and application of international norms. In consideration of “national interest” concept the attribution of international legal policy to international organisations or supranational association is judged as incorrect. The article examines the question of applicability of comparative method in the international law within the discourse among scholars on how differently modern States evaluate international legal norms. Analysis of the tendency to contrasting States’ approaches to the international law encompasses its development from notions “international law of transitional period”, “international legal systems”, to notions “national approach”, “legal style”, “legal culture”. Brief survey of comparative international law gives perspective on diversity of approaches to comparable aspects of the international law. Comparative studies of international legal policy could get consolidated among them.DISCUSSION AND CONCLUSIONS. At first sight the comparative method is hardly applicable to the international law. However the universality of the international law doesn’t exclude variety of approaches to it. The research into international legal policy determined by national interests of every State allows to systemize positions of a State into a single strategy. At the same time comparative method doesn’t only provide classical comparison of States’ positions by issues, but also offers to compare inner-workings of the international legal policy and shaping factors. Nowadays in the context of trends on diversification of international relations (fragmentation, regionalisation), growing popularity of the comparative method translated into comparative foreign relations law and comparative international law. However international legal policy doesn’t correspond with categorial apparatus of comparative foreign relations law. International legal policy is nor able to apply methodological tenets of comparative international law due to its multivalued content. Most likely comparative studies of international legal policy can become a new approach within comparative international law, which should be based on the principles of concreteness and consistency.